Short and long-term results after endovascular management of vascular complications during transfemoral aortic valve implantation - Heger, Thomas; Strauß, Stefanie; Blessing, Erwin; Andrassy, Martin; Erbel, Christian; Müller, Oliver J.; Chorianopoulos, Emmanuel; Pleger, Sven Torsten; Leuschner, Florian; Korosoglou, Grigorios; Bekeredjian, Raffi; Katus, Hugo; et al. (Acta cardiologica, 2017)
Background Vascular injury and access site complications in the contemporary setting of transcatheter aortic valve implantation (TAVI) are known to be associated with increased mortality and morbidity. The aim of our study was to analyse the feasibility and safety of percutaneous treatment of such vascular complications using a stent graft.Methods Between January 2010 and April 2013, 36 TAVI patients developed severe access site complications and underwent subsequent interventional treatment with a covered stent. Acute treatment success was confirmed by angiography immediately after the implantation of the stent graft, with clinical long-term patency follow-up being assessed by duplex ultrasound.Results Of the 36 patients evaluated, percutaneous treatment of the acute access site bleeding was successful in 35 patients (97%), with one patient requiring surgical intervention due to insufficient haemostasis after stent graft implantation. A subset of 5 patients underwent successful ipsilateral stent graft implantation, either because crossover sheath placement was not feasible (n = 1), or intentionally with an even sheathless approach in an effort to reduce vessel injury (n = 4). After a mean follow-up of 22 ± 8 months, stent graft patency was confirmed by duplex ultrasound in 13 patients with an additional 5 patients reporting to be free from symptoms and claudication. Thirteen patients died within the first 24 months after the procedure, however, none was due to access vessel complications. Five patients were lost for follow-up.Conclusions Our data confirm that endovascular treatment of access site complications related to TAVI is feasible, safe and efficacious, resulting in long-term vascular patency.